Strangeness in Relation to Tradition: in the Context of René Guénon’s thought - Jedliński, Marek (Sensus Historiae, 2023)
The article examines the connection between strangeness and tradition in the context of René Guénon’s traditionalist thought. Currently, academic literature lacks the exploration of the discourse of strangeness present in Guénon’s works - hence my research proposal. Guénon, a French thinker, idealized tradition (primordial tradition) and drew inspiration from Eastern wisdom. In this essay, I argue that strangeness is created by tradition, which sets norms and names what is one’s own and what is strange. The definition of what is strange and hostile is therefore determined by tradition. This phenomenon serves to reinforce the significance of communities in cultural contexts where tradition holds sway, and is universal in scope. Drawing inspiration from tradition, contemporary society continues to define strangeness in a similar manner.